Individuals and Institutions in Medieval Scholasticism - Fitzpatrick, Antonia; Sabapathy, John (University of London Press, 2020)
This volume explores the relationship between individuals and institutions in scholastic thought and practice across the twelfth and fifteenth centuries, setting an agenda for future debates. Written by leading European experts from numerous fields, this theoretically sophisticated collection analyses a wide range of intellectual practices and disciplines. Avoiding narrow approaches to scholasticism, the book addresses ethics, history, heresy, law, inquisition, metaphysics, pastoral care, poetry, religious orders, saints' cults and theology. A substantial introduction establishes an accessible historiographical context for the volume's agenda, and a final afterword examines implications for future research. The history of individuals and institutions in scholasticism has often been unhelpfully treated either as a simple intellectual genealogy of schools and doctrines, or a constitutional history of particular organizational forms. This volume advances our understanding by reconsidering these fields as a whole and addressing two large questions. What was the relationship between particular intellectuals and their wider networks? How did individuals alter their institutions, and how did those institutions shape their individuality? This volume is of major importance to intellectual, religious and cultural historians as well as historians of knowledge and science. It will engage those working on individuals and institutions in the middle ages as well as in other periods.